Clinical Study on Treating Acquired Blepharoptosis with Acupuncture and Injection to Some Acupoints - An, Yong Ran; Chae, Myong Chan; Kim, Kwang Hyok; Choe, Il; Jang, Mi; Jo, Hyon Ju; Kim, Jong Hui; Kim, Sung Jin (Medical Science Journal for Advance Research, 2025)
Background: In recent years, acquired blepharoptosis(ptosis) is seen on occasion and may result from high fever and viral infectious diseases. It may present with various symptoms, including visual field obstruction, headache, double vision, and fatigue. Therefore, more and more attention has been paid to early diagnosis and treatment of acquired ptosis. Objective: To observe the clinical effect of acupuncture and injection to some acupoints for acquired ptosis. Methods: 74 patients with acquired ptosis were randomly allocated into a study group with 42 cases (48 eyes) or a control one with 32 cases (39 eyes). The study group was treated with acupuncture and injection to some acupoints, while control group was treated with intramuscular injection of 0.05% proserine and administration of prednisolone. In study groups, 0.2mL of 0.05% proserine was injected to each pts of Chan Zhu (BL2), Yu Yao (EX-HN4), Tong Zi Liao (GB1) once in two days. In addition, in study groups, according to pattern identification, acupuncture was applied on the pts of Ge Shu (BL17), Qi Hai (CV6), San Yin Jiao(SP6) in qi-blood deficiency pattern, Zu San Li (ST36), San Yin Jiao(SP6), Pi Shu (BL20) in spleen qi weakness pattern, He Gu (LI4), Feng Chi (GB20), Tai Chong (LR3) in wind-phlegm pattern, He Gu (LI4), Tai Chong(LR3), Gan Shu (BL18) in qi-blood stagnation pattern. Results: The clinical efficacy was 91.6% in the study group, being significant as compared with the control one (79.6%; p< 0.05). Conclusions: Acupuncture and injection to some pts are effective for acquired ptosis and worthwhile to apply.